Hydrogeochemical characteristics of thermal springs in the Qilian–Haiyuan fault zone at the northeast Tibetan Plateau: Role of fluids and seismic activity - Li, Chenhua; Zhou, Xiaocheng; Li, Jingchao; Liu, Lei; Su, Hejun; Li, Ying; He, Miao; Dong, Jinyuan; Tian, Jiao; Zhou, Huiling; Gao, Gang; Zhang, Caiyan; et al. (Frontiers in Earth Science, 2022)
The Qilian-Haiyuan fault zone (QHF) is located in a highly deformed and seismically active area of the northeastern margin of the Tibetan Plateau. This study investigated the major elements, strontium, hydrogen and oxygen isotopes of 22 sites in the thermal springs along the QHF from October to November 2020. The QHF hydrochemical system is recharged by meteoric water primarily infiltrating between 2.8 and 4.4 km a.s.l. Based on quartz geothermometers, the geothermal reservoir temperature variation ranged from 25.5 to 111.3°C and the circulation depth ranged from 1.3 to 5.6 km. In the QHF zone, the highest spring water temperature values were correlated with deep groundwater circulation circuits in areas where earthquake foci are concentrated. A conceptual model of the hydrologic cycle of thermal springs explains the spatial distribution of earthquakes associated with tectonic movements. The fluid circulation of the QHF corresponds well with the seismicity, which indicates that the hydrological characteristics of the thermal spring in a fault zone are vital in receiving information on seismic activity to assess the seismic risk of the QHF in the future.